The Interplay Between Family Caring Attitudes, Teacher Caring Behaviour, and Psychological Well-Being Among College Students in China: A Conceptual Framework - Xu, Jirong; Bin Raja Ahmad, Raja Azrul Hisham (South Asian Journal of Social Sciences and Humanities, 2025)
This conceptual paper examines the intricate relationship between family caring attitudes, teacher caring behaviour, and psychological well-being among college students in China, with particular attention to the moderating effects of gender and age. Grounded in a comprehensive review of theoretical frameworks, including Self-Determination Theory, Attachment Theory, Family Systems Theory, Social Cognitive Theory, Social Communication Theory, and Noddings’ Caring Education Theory. This paper develops a multidimensional conceptual framework that illuminates how caring dynamics within family and educational environments collectively influence students’ psychological development. The framework conceptualises family caring attitudes as encompassing emotional support, communication, supportive environment, and conflict resolution, while teacher caring behaviour comprises emotional support, teacher-student relationships, academic support, and classroom organisation. These dimensions are theorised to affect students’ psychological well-being across four key domains: self-acceptance, positive relations with others, environmental mastery, and personal growth. The paper further explores how these relationships may be moderated by gender and age, informed by evidence suggesting demographic variations in how students experience and benefit from caring environments. Formulated in the unique cultural context of Chinese higher education, this conceptual framework provides a foundation for future empirical research and the development of targeted interventions to enhance college students’ psychological well being through supportive family and educational environments.